Nursing and the leading role of the user in the CAPS: a study from the constructionist perspective - Hércules Rigoni Bossato; Rosane Mara Pontes de Oliveira; Virginia Faria Damásio Dutra; Cristina Maria Douat Loyola (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To analyze the actions of the Nursing team to promote the leading role of the patient in the Psychosocial Rehabilitation Center. Method: A qualitative study, with reference to Social Constructionism. The study was conducted with 16 members of the Nursing team in two CAPS in the city of Rio de Janeiro from September 2017 to January 2018. The data collected from interviews and observation were organized in the Nvivo Software and the thematic content was analyzed. Results: The study analyzed leading care. This is constructed through creative communication, networking and the perception of the Nursing team as an "antenna". Final considerations: The Nursing team does not reduce the users to the impossibilities of their psychiatric diagnoses, it uses creative communication and the construction of support networks in the territory. It constitutes itself as an antenna in care in psychosocial rehabilitation.